Biochemical Characterizations of the Putative Endolysin Ecd09610 Catalytic Domain from Clostridioides difficile - Hiroshi Sekiya; Hina Yamaji; Ayumi Yoshida; Risa Matsunami; Shigehiro Kamitori; Eiji Tamai (MDPI AG, 2022)
Clostridioides difficile is the major pathogen of pseudomembranous colitis, and novel antimicrobial agents are sought after for its treatment. Phage-derived endolysins with species-specific lytic activity have potential as novel antimicrobial agents. We surveyed the genome of C. difficile strain 630 and identified an endolysin gene, Ecd09610, which has an uncharacterized domain at the N-terminus and two catalytic domains that are homologous to glucosaminidase and endopeptidase at the C-terminus. Genes containing the two catalytic domains, the glucosaminidase domain and the endopeptidase domain, were cloned and expressed in Escherichia coli as N-terminal histidine-tagged proteins. The purified domain variants showed lytic activity almost specifically for C. difficile, which has a unique peptide bridge in its peptidoglycan. This species specificity is thought to depend on substrate cleavage activity rather than binding. The domain variants were thermostable, and, notably, the glucosaminidase domain remained active up to 100 °C. In addition, we determined the optimal pH and salt concentrations of these domain variants. Their properties are suitable for formulating a bacteriolytic enzyme as an antimicrobial agent. This lytic enzyme can serve as a scaffold for the construction of high lytic activity mutants with enhanced properties.